Liberdade e determinismo na arte trágica em Schelling - Carmello, Thaís Bravin (2017)
The German philosopher Friedrich Schelling follows other German Idealists tendency at his time and, from the premise the knowledge of the object belongs to the subjective, makes a philosophical system where in theory both subjective and objective shall equalize each other in order to create an absolute unity. This unity raises as a differential from Kant, also the solution for his lacunes, as well as the basis to the problem of the three works to be treated in this paper: Letters about dogmatism and criticism, System of Transcendental Idealism and Philosophy of Art. These works besides of demonstrating the equalization of subjectivism and objectivism, also includes the aesthetics as the fundamental science for the subject s knowledge, which for Schelling only exists before freedom this, in its pure form, only practicable in the work of art.